New Approach to Improving the Prognosis of Ischemic Stroke by Regulating SCFAs with Acupuncture-Rehabilitation Therapy Based on Gut-Brain Axis - TANG Qiang; LIU Chong; CHAI Fanglei; ZHANG Jinpeng; LI Hongyu; ZHU Luwen (康复学报)
Ischemic stroke is a cerebrovascular disease caused by interruption of cerebral artery blood flow due to various reasons, which would lead to ischemia and hypoxia of local brain tissues and necrosis, and finally corresponding neurological functional defects. Inflammation plays an important role in the progression of stroke.The inflammatory response of ischemic stroke is a dynamic process,which occurs within a short time after ischemia and then affects the central nervous system. The inflammatory reaction has cascade amplification effect, and inflammatory factors can aggravate secondary brain damage, thereby affecting the self-repair of the central nervous system.The elevated levels of inflammatory indicators lead to poor prognosis and a variety of complications. In the study of analgesic mechanism of acupuncture and moxibustion, anti-inflammatory effect of acupuncture is an important aspect that cannot be ignored, which is mainly achieved by hypothalamic-pituitary-adrenal axis (HPA) and autoregulation. Studies have found that acupuncture stimulated different acupoints to activate their own neural pathways, and then the neuroendocrine network took effect. For example,acupuncture-rehabilitation therapy can correct the imbalance of helper T cells/regulatory T cells through the inflammatory pathway, and activate the coding part of interleukin through retinoicacid-related orphan receptor, effectively playing an anti-inflammatory role. In recent years, research teams worldwide have found that there was a close relationship between intestinal flora and cerebrovascular diseases, which can affect the onset and prognosis of ischemic stroke through metabolites or immune mechanisms. Gastrointestinal tract and the brain have a two-way regulatory role, which is abstractly summarized as the gut-brain axis. The two communicate through various channels, such as inflammatory mediators, autonomic nervous system, endocrine system and metabolites of intestinal flora. Short-chain fatty acids (SCFAs) are a kind of metabolites of dietary fiber fermented by bacteria in the colon. They play a key role in maintaining the weak acidic environment of the intestine and anti-inflammatory effect, which can regulate brain function through a variety of pathways. Reduced SCFAs levels in patients with acute ischemic stroke are associated with a significantly higher risk of post-stroke dysfunction. It is found that acupuncture can improve constipation symptoms and fecal characteristics of patients with stroke and increase the concentration of butyric acid and total short chain fatty acid in intestinal flora, and thereby increased the α-diversity index. Mixed SCFAs at appropriate concentration can inhibit lipopolysaccaride (LPS) induced inflammatory response of microglia by regulating the corresponding inflammatory pathway, thus playing an anti-inflammatory protective role. In clinical trials, it has been found that acupuncture rehabilitation therapy can significantly restore the motor function of stroke patients and play the role of antagonizing the inflammatory response after cerebral ischemia, mainly manifested by increasing the amount of beneficial bacteria such as Lactobacillus and Bifidobacterium in the intestine. It can reduce the amount of some opportunistic pathogens such as Clostridium, optimize the structure of intestinal flora, and reduce the expression of key inflammatory factors and tumor necrosis factors involved in central nervous system and autoimmune diseases. In conclusion, from the perspective of gut-brain communication, the mechanism of acupuncture rehabilitation therapy in regulating the intestinal function of patients to reduce the sequelae of stroke is probably related to the metabolism of short-chain fatty acids.